Методологічні аспекти формування трудового потенціалу в процесно-орієнтованому менеджменті - Марчук, Ю. Л. (Ways to Improve Construction Efficiency, 2012)
The paper presents methodological approaches to the essential characteristics of the structure and reproduction potential of employment, the essence of which is to develop theoretical and methodological foundations of most intensive type of expanded reproduction of labor potential based on the theory of neoclassical synthesis and study key areas of national competitive formation of socially oriented economy based on intellectual component human capital.